Hubungan Antara Self Regulated Learning dengan Hasil Belajar Matematika Pada Materi Trigonometri - Rahmi Nindi Arsyad; Sarson W. Dj. Pomalato; Nurhayati Abbas; Novianita Achmad (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the survey research aims to find out the Correlation between self-regulated learning and students’ mathematics learning outcomes in the topic of trigonometry in SMA Negeri 1 Gorontalo. This study focuses on 32 eleventh-grade students in the site area during the academic year of 2018/2019. Moreover, a multiple-choice test was used to collect the data on mathematics learning outcomes, as well as a questionnaire to collect data on self-regulated learning. The hypothesis was tested using the regression and correlational analysis test. The result indicates that self-regulated learning positively correlates with students’ mathematics learning outcomes with the correlational and determination coefficient values of 0.6311 and 40%, respectively. In other words, such a learning model contributes 40% to mathematics learning outcomes; the remaining 60% is influenced by other factors excluded in this research.